Influence of Organisational Structure on Implementation of Electronic Project Monitoring Information System in Public Tertiary Institutions in Kenya - Mburugu, Kirema N.; Mulwa, Angeline S.; Kyalo, Dorothy N. (My University, 2016)
The purpose of this article is to explore the influence of organisational structure on implementation of electronic project monitoring information system (e-ProMIS) in public tertiary institutions. It is based on literature review and filed research by employing crosssectional survey research design. Questionnaire was used to collect data from 30 tertiary institutions and a sample size of 162 members of staff selected through stratified random sampling technique. Null hypothesis was tested using regression analysis at 0.05 confidence interval. The results indicate that all the three types of structure: formalization; complexity; and centralization were statistically significant with coefficients (β=0.238, t=3.167, p=0.002<0.05), (β=0.204, t=2.777, p=0.006<0.05) and (β=0.317, t=4.574, p=0.000<0.05) respectively. Specifically one unit change in implementation of e-ProMIS was associated with 23.8% changes in formalization structure, 20.4% changes in complexity structure and 31.7% change in centralization structure. The overall F statistics was (3,158) = 23.760 at level of significance p = 0.000<0.05 suggesting that there was a statistically significant relationship between organisational structure and implementation of electronic project monitoring information system in public tertiary institutions in Kenya. These study findings imply that for successful implementation of e-ProMIS and other e-government systems, organisational structure is imperative. In this era of digital systems public and private institutions that intend to implement ICT based technologies should ensure that their organisations adopted the right structure that is well aligned to supporting e-government systems.
Keywords: Organisational structure; Implementation; Electronic project monitoring information system; tertiary institutions